LESSONS OF COURSANTS OF MILITARY PENTATHOL - Andres, Andrii; Lototsky, Igor (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Military-applied sports are effective means of physical, moral and psychological training of servicemen for combat activities. A single universal program for training cadets by means of military pentathlon is not described in the special literature. The goal is to summarize the experience of building the training process in military all-around in military universities. 40 coaches of national teams in military pentathlon of 7 universities of Ukraine were surveyed. Results. Physical training of cadets by means of military pentathlon contributes to the formation of their professionalism - it improves applied skills, physical and functional readiness for combat operations. Sports result in military pentathlon to the greatest extent depends on the level of development of athletes' aerobic and speed-power endurance, as well as speed-power qualities. Most often, an obstacle course and throwing are combined in one workout. Regardless of the training period, most of the time is devoted to cross training. Conclusions. The opinions of the coaches on the key issues of building the training process differ significantly, which means that there is no single training methodology for military pentathletes in the universities of Ukraine. Research on the establishment of a scientifically grounded ratio of training volumes of military pentathletes is urgent.